Liner shipping antitrust exemptions in the Pacific rim regions: cartelized markets and the need for international coordination. (8th November 2018) - Wakui, Masako
Abstract: The Pacific Ocean liner shipping market appears to be cartelized, primarily because of antitrust exemptions for shipping companies' agreements. The current industry consolidation trend driven by economies of scale is likely to nurture the collusion inducing environment further; thus, strengthened competition law enforcement associated with the abolition of the exemption system is imperative. The global nature of the service and the experiences thus far indicate the need for internationally coordinated efforts toward that end. This article first explains the current trends in liner shipping services and various factors affecting the market structure to give the readers the appropriate background knowledge to identify the competitive concerns. The next section examines the legal frameworks adopted by countries in the Pacific Rim region, reviews and assesses competition issues, and proposes legislative and enforcement measures necessary to the sector. The article concludes by outlining concrete proposals to be considered by the Asia-Pacific Economic Partnership (APEC).